Perceived Organizational Support and Self Efficacy on Employee Performance: The Mediating Role of Job Satisfaction at PDAM Tirta Hidayah Bengkulu City - Pratiwi, Okta Mustika; Nasution (Jurnal Manajemen, 2026)
Employee performance is a critical factor in achieving organizational success. However, many organizations continue to face challenges related to low productivity caused by ineffective human resource management practices, which may hinder the attainment of organizational objectives. This study aims to examine the effects of perceived organizational support and self-efficacy on employee performance, with job satisfaction serving as a mediating variable among employees of PDAM Tirta Hidayah Bengkulu City. A quantitative research approach was employed, and data were collected through structured questionnaires. The study population consisted of 361 employees, from which 183 respondents were selected using a random sampling technique. Data analysis was conducted using SmartPLS 3.0 software. The findings indicate that perceived organizational support and self-efficacy both have significant positive effects on employee performance and job satisfaction. Furthermore, job satisfaction significantly enhances employee performance. The mediation analysis reveals that job satisfaction partially mediates the relationship between perceived organizational support and employee performance, as well as the relationship between self-efficacy and employee performance. These results suggest that employees who perceive greater organizational support and possess higher levels of self-efficacy tend to experience greater job satisfaction, which in turn contributes to improved performance. This study provides practical implications for strengthening human resource management strategies to enhance employee performance within public utility organizations.